Male orientation on vocalization perches could optimize acoustic signal transmission in anurans. (20th October 2020) - Sandoval, Luis; Barrantes, Gilbert; Protti‐Sánchez, Francesca; García‐Rodríguez, Adrián
Abstract: Acoustic signals are distorted by vegetation, wind currents, or other sounds when transmitted through the environment. Consequently, vocalizations with features that optimize sound transmission or behaviors that improve the efficacy of communication have evolved in many animal species. Among behavioral strategies, some species call from perches above the ground to increase the propagation distance of their acoustic signals. However, the orientation in the perch also influences the transmission of the vocalizations, so that frogs calling from different orientations (i.e., horizontal, upward, or downward) may affect differently the quality and efficacy of sound transmission. We implemented a sound transmission experiment to test for the effect of calling orientation (upward, downward, and horizontal) and distance on the attenuation and degradation of advertisement calls in the common dink frog Diasporus diastema . We broadcasted and re‐recorded advertisement calls at 2 m height, setting the speaker in three directions (upward, downward, and horizontal) to simulate different signaler orientations. We found that attenuation of the advertisement calls is significantly reduced when the speaker was directed either upward or downward, rather than horizontally. However, the degradation of call is lower when the speaker is direct horizontally. Since calls produced from either upward or downward orientations could travel farther, they could be used to signal male spatial location, while calls produced from a horizontal position could provide information on male quality at shorter distances at advanced phases of courtship. Abstract : We implemented a sound transmission experiment to test for the effect of calling orientation (upward, downward, and horizontal) and distance on the attenuation and degradation of advertisement calls in the common tink frog Diasporus diastema . We found that attenuation of the advertisement calls is significantly reduced when males produce their calls upward or downward, rather than horizontally. But degradation is lower when males direct their calls horizontally.